2017
DOI: 10.1002/hep.28975
|View full text |Cite
|
Sign up to set email alerts
|

Targeting β‐catenin in hepatocellular cancers induced by coexpression of mutant β‐catenin and K‐Ras in mice

Abstract: Recently we have shown that co-expression of hMet and mutant-β-catenin using sleeping beauty transposon/transposase leads to HCC in mice that represents around 10% of human HCC. In the current study, we investigate if Ras activation, which can occur downstream of Met signaling, is sufficient to cause HCC in association with mutant-β-catenin. We also tested therapeutic efficacy of targeting β-catenin in HCC model. We show that mutant-K-Ras (G12D), which leads to Ras activation, cooperates with β-catenin mutants… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
67
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 75 publications
(69 citation statements)
references
References 34 publications
2
67
0
Order By: Relevance
“…Wnt/β-catenin is one of several signaling networks that regulate its expression and activity (50), and therefore RNAi-mediated silencing of CTNNB1 is highly effective in HCC preclinical models (51, 52). Interestingly, MEK inhibition has been shown to destabilize MYC protein by regulating its ERK-dependent phosphorylation (53).…”
Section: Resultsmentioning
confidence: 99%
“…Wnt/β-catenin is one of several signaling networks that regulate its expression and activity (50), and therefore RNAi-mediated silencing of CTNNB1 is highly effective in HCC preclinical models (51, 52). Interestingly, MEK inhibition has been shown to destabilize MYC protein by regulating its ERK-dependent phosphorylation (53).…”
Section: Resultsmentioning
confidence: 99%
“…As this signaling pathway can promote both liver injury and regeneration, therapies targeting Wnt/β-catenin signaling must be carefully evaluated to consider both the disease context and the targeted cell type. For example, targeting Wnt/β-catenin signaling may be a viable therapeutic option for liver cancer with oncogenic β-catenin signaling (119, 120). However, targeting Wnt/β-catenin signaling in HSCs to reduce ECM deposition in liver fibrosis may potentially be effective (186188), but other studies indicate that it could potentially exacerbate fibrogenesis by promoting HSC activation (184, 185).…”
Section: Discussionmentioning
confidence: 99%
“…These mice developed HCC with gene expression profiles that displayed high correlation with the gene profiles of a subset of human HCC patients with both CTNNB1 mutations and Met activation signatures (118). To address if Ras activation downstream of Met could be contributing to Met-β-catenin HCC, G12D- KRAS and mutant-β-catenin were expressed using SB-HTVI, which also yielded HCC with approximately 90% molecular similarity to Met-β-catenin HCC (119). In fact, treatment of these mice with lipid nanoparticles containing small interfering RNA (siRNA) targeting CTNNB1 yielded a significant decrease in tumor burden (119).…”
Section: Cell Type–specific Roles Of Wnt/β-catenin Signaling In Livermentioning
confidence: 99%
See 1 more Smart Citation
“…GS is a target of the Wnt/beta‐catenin signal pathway in the liver, and the expression of GS is regulated by translocation of beta‐catenin from the cytoplasm to the cell nucleus, which indicates the activation of the Wnt/beta‐catenin signal pathway . Recently, studies have shown that activation of this pathway contributes to carcinogenesis and epithelial–mesenchymal transition (EMT) in HCC . Therefore, it is logical to speculate that GS might play a critical role in HCC progression.…”
Section: Introductionmentioning
confidence: 99%